La Serviciabilidad en las vías rurales del cantón Cuenca mediante dos alternativas de medición. - Quizhpi Guaman, Juan Pablo (2024)
Currently, to establish road maintenance, the entities responsible for it rely on established technical indicators that measure the quality of service and comfort perceived by users without considering user opinion. Therefore, this research focuses on determining the Serviceability of the 4 second order roads in the Cuenca Canton, based on two approaches. The first approach allows determining the calculation of the International Roughness Index (IRI) using therlin profilometer, which, being an easy-to-use and cost-effective equipment, has a simple analysis method with reliable results that allows analyzing the condition of the pavement surface layer, based on the calculated IRI, the Present Serviceability Index (PSI) was determined, thanks to the equation established by Al-Omar and M.I Darte. The second approach focuses on the application of the Servqual Model, involving user participation through a survey indicating how they perceive the service of this resource, which is measured through 4 dimensions: reliability, responsiveness, assurance and empathy. Once the Serviceability was determined by the PSI Method and the Servqual Model, a relationship was developed using the Pearson correlation coefficient between these two variables, yielding a value of 0.988, indicating a strong positive relationship between the variables. This allows us to determine prediction equations that can be applied in the study of second-order roads by the entities responsible in an agile and cost-effective manner.